Feminist Undercurrents in the Poetry of Sylvia Plath: Resistance, Identity, and Agency - Suman, Shambhunath (Journal of Advanced Research in Humanities and Social Sciences, 2025)
This article explores the profound feminist undercurrents in the poetry of Sylvia Plath, focusing on the central themes of resistance, identity, and agency. It argues that while Plath may not have selfidentified as a political feminist in the modern sense, her work is a powerful testament to the struggle against patriarchal oppression and a courageous exploration of female selfhood. The article highlights how Plath’s poems engage in acts of resistance, from the symbolic “killing” of male authority figures in “Daddy” to the rejection of societal norms of domesticity and marriage. It further examines her relentless search for a coherent female identity, one not defined by male gazes or conventional roles. This quest for a liberated self is intrinsically linked to the theme of agency, where the speaker reclaims her power through the act of writing, the embrace of anger and rage, and the defiant declaration of self-possession, most famously in “Lady Lazarus”. The article concludes that Plath’s unique contribution lies in her ability to transform personal trauma into a universal language of female defiance and self-creation, making her a crucial, albeit controversial, figure in feminist literary history.